Elucidating influence of strategic integrated weed management on weed incidence, growth and productivity of kharif maize (Zea mays L.) - Mandal, Diyan; Ghosh, Probir Kumar (The Indian Journal of Agricultural Sciences, 2026)
During rainy (kharif) season of 2022-23, a field experiment was conducted at ICAR- National Institute of Biotic Stress management to study the integrated impact of rice straw mulch and new generation herbicides on dynamics of weeds and maize growth as well as yield. Rice straw mulch application provided effective weed control and fetched higher grain yield when compared to no mulch treatment. Atrazine PE followed by use of tembotrione PoE and topramezone PoE, respectively, significantly decreased density and dry matter of weeds per unit area thereby offering higher weed control efficiency. The results evinced that 8 t ha-1 rice straw mulch in combination with atrazine PE + tembotrione PoE provided better control bringing about higher grain yield and net return.